Stokes, Ed., From Stalinism To Pluralism - A Documentary History Of Eastern Europe Since 1945 - Jaeckel, Nancy (Teaching History: A Journal of Methods, 1992)
This book was created from documents Professor Stokes gathered to assist his students in understanding what had happened in the autumn of 1989 with the fall of the Berlin Wall and to help students realize that those events had not occurred spontaneously or in a vacuum. The volume should prove useful to both students and teachers, since many concepts of communism and Stalinism are difficult to understand. While to call the book timeless would be an exaggeration, Professor Stokes has provided a book that should continue to have relevance as events continue to unfold in the Soviet world.